Increased ID4 expression, accompanied by mutant p53 accumulation and loss of BRCA1/2 proteins in triple‐negative breast cancer, adversely affects survival. Issue 5 (2nd November 2015) - Thike, Aye A.; Tan, Puay H.; Ikeda, Murasaki; Iqbal, Jabed
Abstract : Aims: Breast cancer 1 (BRCA1) expression is down‐regulated in a significant proportion of non‐hereditary breast cancers, in the absence of any mutation. This phenomenon is more pronounced in oestrogen (ER)‐negative tumours. Recent studies have suggested that inhibitor of DNA binding 4 (ID4), as well as p53, participate in the transcriptional regulation of BRCA1. Methods: Immunohistochemical expression of ID4, BRCA1, BRCA2 and p53 in 699 women with triple‐negative breast cancer was investigated using tissue microarrays. The prognostic role of these biomarkers was also evaluated. Survival outcomes were estimated with the Kaplan–Meier method and compared between groups with log‐rank statistics. Results: Loss of BRCA1 and BRCA2 expression and overexpression of ID4 and p53 was observed in 75%, 90%, 95% and 66% of tumours, respectively. ID4 expression was increased in higher tumour grade ( P < 0.001) and was associated significantly with basal‐like subtype ( P < 0.001), BRCA2 down‐regulation ( P = 0.037) and p53 accumulation ( P < 0.001). Patients with strong ID4 expression displayed worse disease‐free survival in both triple‐negative breast cancers ( P = 0.041) and basal‐like triple‐negative breast cancers ( P = 0.026). Conclusion: There is frequent ID4 expression and concomitant loss of BRCA proteins in triple‐negative breast cancer. We hypothesize that strong ID4 expression could be useful as a prognostic marker in triple‐negative breast cancer, predicting early tumour recurrence.